The old way [videorecording (DVD)] - Lucas, Carl W.; Cage, Nicolas, 1965-; Armstrong, Ryan Kiera; Le Gros, Noah; Howard, Clint, 1959-; Benrubi, Abraham, 1969-; Knuppe, Kerry, 1983-; Searcy, Nick; Fernandez, Shiloh, 1985- (Lionsgate, 2023)
An old gunslinger and his daughter must face the consequences of his past, when the son of a man he murdered years ago arrives to take his revenge.